(untitled) (Asian Journal of Medical and Biological Research, 2020)
This study was conducted under the Department of Physiology and Pharmacology to determine the effects of Neem and Nishyinda leaves supplementation on growth performance and GUT biosis in broilers. A total of 40 day old broiler chicks were divided into four groups A, B, C and D. Group A was considered as control, fed only with commercial broiler ration. Group B supplemented with formulation of 2 gm grinded Neem leaves, Group C with 2 gm grinded Nishyinda leaves and Group D with 1 gm grinded Neem leaves plus 1 gm grinded Nishyinda leaves per liter of water respectively. Observations were recorded for live body weight, weight gain, feed consumption, feed efficiency, hemato-biochemical parameters and GUT biosis specially the parasite of birds in six weeks. Body weights were increased significantly (p<0.05) in all treated groups in respect to the control and highest was recorded in combine Neem plus Nishyinda supplemented groups (Group D). No significant (p>0.05) differences were observed among the groups for PCV and TEC values. Hb content increased and ESR decreased significantly (p<0.05) with combine Neem plus Nishyinda supplemented group (Group D). The serum SGOT and SGPT levels were also decreased with the same kind of supplementation. In treatment group there was significantly decreased of parasitic eggs, but in case of control group no decrease of parasitic eggs. There was no significant pathological change in any internal organs of the broiler of treated groups. Best result was found in the group D. The present study reveals that combine supplementation of Neem plus Nishyinda gives better result over other groups in respect to body weight gain, feed conversion ratio, hemato-biochemical parameter and profitability without making any health hazard of the broilers. Asian J. Med. Biol. Res. June 2020, 6(2): 168-175